Mucolitic Ambroxol Versus Hypertonic Saline Nebulizer Induction: For Increasing Sputum Volume And Finding Acid-Fast Bacilli - Sunarto Ang; Sumardi -; Erna Kristin (Pusat Kedokteran Tropis, 2012)
Introduction: Tuberculosis, a major killer disease in the community, was caused by Mycobacterium tuberculosis. According to WHO (2006), pulmonary tuberculosis cases in Indonesia was third ranked in the world. Prevalence of pulmonary tuberculosis in Eastern Indonesia was higher than in Java and Bali, but the findings of positive smear was lowest. AFB discovery will be decreased because of the poor quality and quantity of sputum.The useful of mucolitic ambroxol or hypertonic saline nebulizer induction will be to increase quality and quantity of sputum smear.Objectives: The aim of this study was to determine and to compare the effectiveness of ambroxol and use a hypertonic saline induction on new suspected pulmonary tuberculosis patients to increase sputum volume and to find AFB.Methods: 76 new suspected pulmonary tuberculosis patients were divided into 2 groups with doubleblind and open-label simple randomsampling RCT (Randomized Controlled ClinicalTrial-Parallel design) study.The sputum induction using ambroxol or 3%hypertonic saline solution.The primary and secondary outcome were increasing sputum volume and finding AFB by Ziehl-Neelsen staining to calculate the AFB count per 100 fields of view. Non parametric statistical analysis and percentage of success.Results: All patients can produce sputum. Only one patient ambroxol group can’t produce it.The quality and quantity of sputum hypertonic saline induction volume better than ambroxol. AFB finding increaseboth groups, but no significant difference. AFB finding increase 26.47%(9/34)with ambroxol and 27.78% (10/36)with hypertonic saline induction compared than previous negative smear.Conclusions: Significant differences increase sputumvolume hypertonic saline induction compared than ambroxol.No significant difference AFB finding improvement hypertonic saline induction compared for ambroxol. Finding AFB increase 26.47% with ambroxol and 27.78% with hypertonic saline induction compared previous negative smear.Keywords: Tuberculosis, Ambroxol, Nebulizer induction, Sputum volume, AFB